Patterns of vegetation composition across levels of canopy disturbance in temperate forests of west Himalaya, India - Airi, Subodh; Rawal, Ranbeer S. (Biodiversity: Research and Conservation, 2017)
This study analyses the impacts of canopy disturbance on vegetation compositional attributes of two characteristic temperate forests (i.e., mixed broad-leaf and banj-oak forests) in west Himalayan part of India. Following the standard approaches, quantitative information on compositional attributes of forest vegetation was generated and analyzed. Considerable changes in these attributes were revealed across different levels of canopy disturbance in both forests. In particular, tree density and total basal area (TBA) exhibited significant decline from undegraded to degraded stands. Among others, seedling and sapling density of mixed broad-leaf forest was affected adversely by increased level of canopy disturbance. However, herb density in this forest increased significantly with increasing levels of disturbance; the same was not true for banj-oak forest. A significant decline in relative frequency and density of native herbaceous species was apparent towards degraded stands, implying that the disturbed sites in both forests created an opportunity for the establishment and proliferation of non-natives. However, with significant increase in relative density of non-native herbs, the degraded stands of banj-oak forest emerged as critically vulnerable to non-native proliferation. The patterns of tree size class distribution in both forests also exhibited certain trends across canopy disturbance, which suggested possible future changes in composition. In particular, the patterns of common tree associates (i.e., Myrica esculenta and Rhododendron arboreum) in banj-oak forest and Pinus roxburghii in mixed broad-leaf forest were indicative of likely compositional changes in near future. The study concludes that: (i) compositional attributes of both mixed broad-leaf and banj-oak forests were sensitive to increasing levels of canopy disturbance, (ii) mixed broad-leaf forest exhibited greater sensitivity to canopy disturbance at recruitment levels, (iii) increased canopy disturbance led to establishment and proliferation of non-native species in the herbaceous layer of both forests, and (iv) banj-oak forest exhibited high vulnerability to non-native proliferation at degraded stage.